Determinan akuntabilitas pengelolaan dana desa di kabupaten purworejo - Murti, Woro Ayuda; Maharani, Betari (Universitas Muhammadiyah Magelang, 2023)
This research aims to empirically test the influence of village apparatus competence, community participation, the use of information technology, interal control systems and accounting information systems on accountability in managing village funds in villages throughout Kemiri District, which consists of 40 villages. This research is quantitative research using survey technique. The data source in this study used primary data which was collected using a questionnaire using a purposive sampling method, so that the sample obtained was 78 respondents consisting of village heads, village secretaries and treasurers or financial officers. The results of this research show that the competency variable of village officials has a positive effect on the accountability of village fund management. Meanwhile, community participation, use of information technology, internal control systems and accounting information systems show results that do not affect the accountability of village fund management